Medellín: A Igreja no tempo e no lugar certo - Brighenti, Agenor (Revista Eclesiástica Brasileira, 2018)
Medellín é fruto de uma Igreja no tempo e no lugar certo. Foi uma ousadia da Igreja na América Latina, que continua fazendo caminho, 50 anos depois. Bispos proféticos, catalisadores de um conjunto de iniciativas arrojadas e assessorados por teólogos e pastoralistas de primeira grandeza, desencadearam um processo eclesial que mudaria radicalmente o perfil da Igreja na América Latina. Para o Autor, os fatores que possibilitaram a realização da II Conferência são basicamente quatro: o momento de profundas transformações da década revolucionária de 1960; uma Igreja sintonizada com seu momento histórico e atenta aos novos sinais dos tempos; a renovação do Vaticano II, do qual Medellín foi uma “recepção criativa”; e o fato de Medellín ter feito do Concílio mais um “ponto de partida” do que um “ponto de chegada”. Abstract: Medellín is fruit of a Church that is at the right time and in the right place. It was a daring movement of the Latin American Church, a Church that still continues to follow this path fifty years later. Prophetic bishops, catalytic agents of a set of daring moves and assisted by theologians and pastoralists of first magnitude, launched an ecclesial process that would radically change the Latin American Church’s profile. For the Author, the factors that made possible the realization of the II Conference are basically four: the moment of deep transformations in the revolutionary decade of 1960; a Church in tune with its historical moment and alert to the new signs of the times; the Vatican II’s renovation, of which Medellín was a “creative reception” and the fact that Medellín made of the Council a “starting point” rather than “a point of arrival”. Keywords: Church; Latin America; Vatican II; Medellín; Poor.